Pain in focal dystonias – A focused review to address an important component of the disease. (September 2018) - Avenali, Micol; De Icco, R.; Tinazzi, M.; Defazio, G.; Tronconi, L.; Sandrini, G.; Tassorelli, C.
Abstract: Focal dystonia is characterized by involuntary muscle contractions that cause abnormal postures and/or twisting movements in a segment of the body. Motor symptoms have a major impact on disability in this condition, but the presence of pain represents an additional source of impairment and poor quality of life. Notwithstanding that pain occurs in up to 70% of patients with cervical dystonia and in a relevant proportion of subjects with focal dystonia of the limbs, it has received very little attention from researchers and controlled trials are scant. The aim of this review is to summarize the current knowledge on the clinical assessment and management of pain in focal dystonias. The search results will inform on the types of pain reported in focal dystonias, on the tools that are used to quantify pain and on the efficacy of pharmacological and non-pharmacological approaches. The collated data will hopefully improve the clinical management of focal dystonia and also stimulate future research on dystonia-associated pain. Optimization of the outcome indeed requires the identification and the management of all the factors that determine disability and hence relies on a multidisciplinary approach. Highlights: Pain is a disabling non-motor symptom in patients with focal dystonias. The CCDRS is a validated and reliable scale to assess pain in cervical dystonia. Botulinum toxin is the only effective treatment in relieving painful symptoms. Data collected should improve clinical management of dystonia-associated pain. Controlled trials are needed for the identification of specific pain treatments.